The gut–brain axis in Alzheimer’s disease is shaped by commensal gut microbiota derived extracellular vesicles - Junhua Xie; Lien Van Hoecke; Elien Van Wonterghem; Griet Van Imschoot; Vanessa Andries; Lars Vereecke; Roosmarijn E. Vandenbroucke (Gut Microbes)
Emerging clinical and experimental evidence highlight the involvement of gut microbiota in the onset and progression of neurodegenerative diseases such as Alzheimer’s disease (AD) via neuroinflammatory processes along the gut–brain axis. Despite this, the precise mechanisms governing gut microbial involvement in AD remain elusive. In this study, we observed that AppNL-G-F AD mice raised under germ-free (GF) conditions, display a reduced amyloid-β (Aβ) pathology, accompanied by a shift in microglial cells toward a less inflammatory state and increased phagocytotic efficiency. In addition, we demonstrate that gut microbiota depletion can protect against synaptic deficits in AD mice. Notably, administering bacterial extracellular vesicles (bEVs), i.e. nano-sized particles packed with bacterial components, derived from fecal slurry from specific pathogen-free housed AppNL-G-F AD mice, reversed the effects of GF conditions on both microglial activation and Aβ plaque accumulation. These findings reveal for the first time that commensal gut microbiota-derived bEVs have a major impact on AD pathology progression.